Phenotypic characterisation of Listeria monocytogenes in cow milk from three catchment areas of Goliati Area in Thyolo District, Malawi - Manuelo, Chrissy; Mwinjiro, Agathar; Masangwi, Danger; Bandawe, Gama; Madanitsa, Mwayiwawo; Kazembe, Yohanne; Kamaliza, Mada; Ntenda, Peter Austin Morton; Mandala, Wilson; Chigwechokha, Petros; Mtewa, Andrew G; Mwenyenkulu, Tisungane Edward (Archives of Community Medicine and Public Health, 2021)
Background: School closures were mandated in response to COVID-19 as a nonpharmaceutical intervention. Influenza A was widespread in Wisconsin at the time of mandate, March 18, 2020, allowing its evaluation for influenza interruption. Methods: Daily percent positivity of influenza A among primary care patients who received a rapid influenza diagnostic test was evaluated throughout two influenza seasons while schools were open and closed. Results: Median deviation from baseline of percent positivity was significantly lower when schools were closed than when open (-2.25% vs 1.08%; H=7.84; P=0.005). Median deviation in percent positivity for the eight days following statewide school closure was -20.0. Discussion: Unprecedented closures of all Wisconsin schools was associated with a rapid decline in influenza A. Additional evaluations within other jurisdictions are warranted.